Pengaruh Current Ratio, Debt To Equity Ratio, Debt To Asset Ratio, Dan Working Capital Turnover Terhadap Return On Asset Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2021-2023 - Rizal, Muhammad; Anam, Hairul; Makherta Sutadji, Ika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This research aims to examine the influence of Current Ratio, Debt to Equity Ratio, Debt to Asset Ratio, and Working Capital Turnover on Return on Assets. The data used in this research are the annual financial reports of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period. The type of research used is quantitative research. The sampling technique used a purposive sampling method which produced 197 company samples with a total population data obtained of 251 from 3 periods. The data analysis method used is descriptive statistical analysis and multiple linear regression analysis. The test equipment used is the classical assumption test, coefficient of determination test and t test. The results of this research state that the Current Ratio has an effect on Return On Assets. Meanwhile, Debt to Equity Ratio, Debt to Asset Ratio, and Working Capital Turnover have no effect on Return On Assets.